Monster blood - Stine, R. L.; Stine, R. L.; Gonzalez, Maddi (Goosebumps graphix., 2025)
While staying with his great-aunt Kathryn, Evan Ross visits an eerie old toy store. Among the dusty shelves, he finds a can of something called "Monster Blood." The odd, sticky substance really does look like the blood of a creature. It has a greenish glow and sometimes feels warm to the touch. But the most alarming thing about the toy ooze is the way it keeps growing-overflowing its container, then a bathtub, then filling up a whole trash can. Evan worries that all that growing has given the Monster Blood a monstrous appetite...